Soluble urokinase plasminogen activator receptor (suPAR) predicts 2-year cardiovascular events in patients after acute chest pain. (25th November 2020) - Chew-Harris, J; Appleby, S; Troughton, R.W; Richards, A.M; Pemberton, C.J
Abstract: Background: Soluble urokinase plasminogen activator receptor (suPAR) is an emerging biomarker of sub-inflammation related to plaque instability. Its modulation may reflect on immune dysfunction related to cardiovascular (CVD) outcomes. We assessed the prognostic performance of suPAR to predict 2-year clinical outcomes in patients with acute chest pain, suspicious of acute coronary syndromes. Methods: A total of 812 patients presenting to the emergency department with the primary complaint of acute chest pain were prospectively recruited. Baseline suPAR concentrations were measured at presentation using the ViroGates CE-marked ELISA. Standard cardiac markers including hsTnT and NT-proBNP (both Roche) were also measured. Data for all biomarkers were treated as continuous and expressed as median [interquartile range (IQR)]. Statistical assessment was made using SPSS v25 (IBM). Groups were compared by Mann-Whitney U test/Spearman's rho. Prognostic performance of suPAR in comparison with hsTnT and NT-proBNP to predict the primary outcomes of new myocardial infarction (MI), new heart failure (HF), all cause readmission, and the composite of major adverse cardiac events (MACE) were assessed using binary logistic regression after the adjustment of traditional risk factors. Results: In the entire chest pain cohort [median age: 63 yrs (IQR: 54–74), 34% female], 156/812 of patients had adjudicated AMI [STEMI (n=22)/NSTEMI (n=134)]. suPAR concentrations were found to be lower in males (Spearman's Rho, r=−0.17, P<0.0001) and in those with eGFR ≥60mL/min/1.73m 2 (n=439) (r=−0.40, P<0.0001), but elevated in those older than 65 years (n=372) (r=0.55, P<0.0001). During the 2-year follow-up period, there were 54 fatalities, 287 recorded as having new CVD events, 46 diagnosed with new heart failure, 71 with new MI (66 NSTEMI/5 STEMI), 54 with new unstable angina, 126 patients classified with MACE and 190 patients who were readmitted into hospital within 1-year from presentation. In logistic regression analyses, the odds ratio (OR) of suPAR; 8.5 (95% CI:1.8–40.9) to predict a 2-year event (for example new total CVD events) was stronger than hsTnT; OR: 1.2 (95% CI: 0.9–1.5) and NT-proBNP; OR: 0.8 (95% CI:0.8–1.3) (P<0.0001) (Figure). Further, incorporation of baseline suPAR values into multivariate models for predicting events, such as MACE at 2-years (adjusted for age, gender and eGFR), resulted in an improvement in the C-statistic from 0.72 to 0.76. Conclusion: In this acute chest pain cohort, suPAR concentrations are independent predictors of cardiovascular outcomes at 2 years. suPAR may add value in the risk assessment of patients with acute chest pain. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Health Research Council of New Zealand, National Heart Foundation of New Zealand